PERANCANGAN LOGO MASTER FITNESS CENTER DAN AEROBIC - SRI WAHYUNI, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Master Fitness Center and Aerobic identity is just a writing name “Master Fitness Center and Aerobic” only. This problem makes the logo that represent image and character has not created yet. It will also make the Master Fitness Center and Aerobic identity is not strong enough. The design aims to create a logo as identity that represent image of Master Fitness Center and Aerobic. The different visual elements will be determined so it will be easily recognized by audiens. Logo design are logotype and logogram.Design method used is glass box method. Glassbox is designing that is done rationally and logicly. The method starts from data collection, interview, and observation. Analysis approach used is SWOT analysis (strenght, weakness, opportunites, threats).Master Fitness Center and Aerobic logo design is poured in manual book as main media. Support medias are x-banner, poster, sticker, name card, member card, flyer, t-shirt, drinks bottle which are aim to strengthen the main media application.Keyword: Logo Design, Master Fitness Center and Aerobics, Media